Analyzing the Underlying Structure of Online Teaching During the COVID-19 Pandemic Period: An Empirical Investigation of Issues of Students - Shaukat, Muhammad Zeeshan; Niazi, Abdul Aziz Khan; Qazi, Tehmina Fiaz; Basit, Abdul (Frontiers in Psychology, 2021)
Aim of the study is to disentomb the underlying structure of issues of university students taking online classes during COVID-19 pandemic period. Overall design of the study encompasses on a review of contemporary literature, field survey for data collection and analysis. Discourse of literature coupled with expert opinion has been employed for identification of issues. Interpretive Structural Modeling (ISM) is used for determination of intra-issue relationships and analyzing the underlying structure. Cross impact matrix multiplication applied to classification (MICMAC analysis) is used as a technique for classifying issues on the basis of deriving-dependence power. Results of literature show that there are twenty-one major issues faced by the students taking online classes. ISM shows that lack of institutional guidelines, lack of regulators’ guidelines, stress of pandemic situation and abrupt (not planned) start of online classes are the most critical issues. MICMAC analysis reveals that there is no autonomous issue, four (i.e. connectivity issue, shy to use technology, lack of institutional guidelines and stress of pandemic situation) are independent, other six issues are dependent and remaining eleven are linking. This is a valuable study having practical implications for regulators, students, parents and society for understanding the current problem. It is an original attempt that contributes towards literature in form of a structural model and a diagram of classification of issues.